Preparation method and application of doping regulation defect-containing MoO3 (at) NiCo-LDH (layered double hydroxide) polyaniline core-shell nano composite array material
By doping and controlling the preparation of MoO3@NiCo-LDH@polyaniline core-shell nanocomposite array material, the problem of poor conductivity and cyclic stability of photoelectric information materials in actual applications is solved, and the specific capacitance and photoelectric catalytic performance are improved. Suitable for supercapacitors and lithium-ion batteries.
Patent Information
- Application Number
- CN202411361073.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-27
AI Technical Summary
In actual applications, existing photoelectric information materials have problems such as electrical conductivity, poor cyclic stability performance, low specific capacity and poor photoelectric catalytic effect.
The preparation method of MoO3@NiCo-LDH@polyaniline core-shell nanocomposite array material is used to prepare MoO3@NiCo-LDH@polyaniline core-shell nanocomposite array material, and the low-temperature water bath heat method, cryogenic method and electrodeposition method are used to form defect-rich The core-shell structure combines plasma processing technology to optimize the conductivity and photoelectrocatalytic properties of the material.
It significantly improves the specific capacitance, conductivity and photoelectric catalytic performance of the material, providing a broader application prospect, especially in the fields of supercapacitors, lithium-ion batteries and photoelectric catalysis, which show excellent cycling stability and electrochemical performance.
Smart Images

Figure CN119242038A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a core-shell nano composite array material. Background Art
[0002] Optoelectronic information functional materials have broad application prospects in the fields of optics and electrical energy storage, such as electrochemical capacitors, electrochromic smart windows, lithium-ion batteries, and photoelectrocatalysis. However, the performance of a single material is limited in practical applications, and it is necessary to improve the material performance by doping or compounding and designing the material structure, and then combining the synergistic effect of different component materials. Material selection and structural design are the key to improving optoelectronic performance. Among many inorganic and organic materials, MoO 3 It has excellent redox activity and good rate performance and cycle stability as an electrode material. 3 The specific capacitance of the material and the electrical conductivity as a metal oxide are not ideal, and the performance of photocatalytic degradation of dyes is also very much to be improved, and there is a large gap from practical application. In order to overcome these shortcomings, the present invention uses NiCo-LDH (nickel cobalt layered double hydroxide) and polyaniline (PANI) as auxiliary materials. NiCo-LDH has good charge conductivity, high capacitance and electrochemical activity, which helps to improve the electrical conductivity and energy storage capacity of the material. As a conductive polymer, polyaniline not only has excellent electrical conductivity, but also has good mechanical flexibility and environmental stability, which can further enhance the electrical conductivity and mechanical properties of the composite material. The present invention can form a core-shell nanostructure by compounding MoO3, NiCo-LDH and polyaniline. This composite material significantly improves specific capacitance, electrical conductivity and photoelectrocatalytic performance through the synergistic effect between each component, providing a broader prospect for it in practical applications. Summary of the invention
[0003] The purpose of the present invention is to solve the problems of poor conductivity, cycle stability, low specific capacity and poor photoelectrocatalytic effect of existing optoelectronic information materials in practical applications, and to provide a doped and regulated defective MoO 3 @NiCo-LDH@ Preparation method and application of polyaniline core-shell nanocomposite array materials.
[0004] A doping-controlled defect-rich MoO 3 The preparation method of @NiCo-LDH@ polyaniline core-shell nanocomposite array material is specifically completed in the following steps:
[0005] 1. Preparation of MoO by low temperature water bath thermal method 3 :
[0006] ①. Put Na 2 MoO4 The powder was added to deionized water and stirred for a while to obtain Na 2 MoO 4 Aqueous solution;
[0007] ② Use concentrated sulfuric acid or concentrated hydrochloric acid and water to prepare an acidic solution with a pH value of 1 to 6.5;
[0008] ③. Add an acidic solution with a pH value of 1 to 6.5 dropwise into the Na 2 MoO 4 The aqueous solution is stirred for a period of time to obtain a mixed solution; the mixed solution is heated at 40°C to 85°C for a period of time, and then cooled to room temperature to obtain a reaction product; the reaction product is washed and then dried to obtain MoO 3 powder;
[0009] 2. Preparation of ion-doped defect-rich MoO by cryo-preparation 3 @NiCo-LDH core-shell structure material:
[0010] ①、MoO 3 The powder, nickel salt, cobalt salt, alkaline substance and metal salt are added into deionized water, and ultrasonically mixed to obtain a precursor mixed solution;
[0011] ② Place the precursor mixed solution in a freeze dryer and freeze dry for a period of time. After the temperature of the reaction product returns to room temperature, wash, dry and plasma treat the reaction product. Finally, calcine at 350℃~850℃ for 2h~30h to obtain ion-doped defect-rich MoO 3 @NiCo-LDH core-shell structure material;
[0012] The specific process parameters of the plasma treatment described in step 2② are: using plasma technology, introducing oxygen gas, the treatment power is 100W to 1000W, and the treatment time is 5min to 30min;
[0013] 3. Preparation of MoO by Electrodeposition 3 @NiCo-LDH@Polyaniline core-shell nanocomposite array materials:
[0014] ①, adding polyaniline and lithium perchlorate into deionized water to obtain a deposition solution;
[0015] ② Ion-doped defect-rich MoO 3@NiCo-LDH core-shell structure material is used as working electrode, Ag / AgCl is used as reference electrode, and Pt sheet is used as counter electrode. The working electrode, reference electrode and counter electrode are immersed in the deposition solution, and the deposition treatment is carried out for a period of time by constant current method. Then the working electrode is taken out, cleaned, dried, and finally annealed at 350℃~850℃ to obtain MoO 3 @NiCo-LDH@polyaniline core-shell nanocomposite array material;
[0016] 4. MoO 3 The surface of @NiCo-LDH@ polyaniline core-shell nanocomposite array material was plasma treated to change the surface properties and obtain doped and regulated defect-rich MoO 3 @NiCo-LDH@polyaniline core-shell nanocomposite array material;
[0017] The specific process parameters of the plasma treatment described in step 4 are: using plasma technology, introducing oxygen gas, the treatment power is 10W to 1000W, and the treatment time is 5min to 30min.
[0018] A doping-controlled defective MoO 3 @NiCo-LDH@polyaniline core-shell nanocomposite array materials are used as electrode materials in supercapacitors, lithium-ion batteries or zinc-ion batteries.
[0019] The product of the present invention contains MoO 3, and the prepared NiCo-LDH and polyaniline are used as electrode materials. By regulating the doping and regulating the material to contain an appropriate amount of defects, combined with the synergistic effect between different components of the material, the photoelectric performance of the material is significantly improved. In addition, through plasma treatment, the crystal structure of the product also produces oxygen defects, the material lattice expands, and the lattice binding energy changes; this is conducive to the formation of lattice defects, the generation of oxygen defects and the improvement of conductivity and hydrophilicity, and the increase of active center sites, which stimulates the resonance effect between ions; the conductivity is improved by regulating the concentration of semiconductor carriers, thereby optimizing the electrochemical performance of the product. Finally, the three-dimensional core-shell structure has a large specific surface area. A layer of polyaniline is coated on the outer layer of the product, which can effectively increase the contact with the electrolyte, protect the internal electrode material structure and enhance the conductivity, and rely on the synergistic coordination of multiple metals to improve the transmission rate of lithium ions, thereby achieving both corrosion resistance and good conductivity, and direct contact with the electrolyte, reducing the corrosion of the electrolyte and inhibiting the occurrence of side reactions. In addition, polyaniline conductive polymers have good electrical conductivity. This has a positive significance for improving the overall electrochemical performance of the product. The nanomaterials prepared in the experiment have good electrochemical properties and have potential application value in supercapacitors, lithium-ion batteries, zinc-ion batteries, electrochromism and photoelectrocatalysis.
[0020] The present invention regulates MoO by doping 3 @NiCo-LDH@ polyaniline forms defects to improve the excellent photoelectric properties of the material. The preparation method and application of the material include the following beneficial effects:
[0021] 1. Ion doping and regulation of defective MoO prepared by the present invention 3 The entire synthesis process of @NiCo-LDH@ polyaniline core-shell structure nanomaterials is safe, pollution-free, and the operation process is relatively simple. This core-shell structure has a large specific surface area, which increases the contact area with the electrolyte, can effectively shorten the distance of electron separation and transfer, and improve the diffusion coefficient of ions moving inside; at the same time, this core-shell structure also increases the specific surface area and active sites, providing favorable conditions for enhancing electrochemical performance;
[0022] 2. Ion doping and regulation of defective MoO prepared by the present invention 3 @NiCo-LDH@ polyaniline core-shell nanocomposite array material has good wettability in alkaline aqueous solution, is easy to fully contact with the electrolyte, and exhibits good cycle stability;
[0023] 3. The ion doping and plasma treatment technology in the present invention together lead to the preparation of materials rich in oxygen defects, thereby optimizing the conductivity and hydrophilicity of the composite material;
[0024] 4. The three-dimensional core-shell structure and the coating of the polyaniline conductive polymer in the present invention effectively buffer the volume change of the electrode material during the reaction and avoid direct contact with the active material, thereby reducing the occurrence of side reactions;
[0025] 5. Ion doping and regulation of defective MoO prepared by the present invention 3 @NiCo-LDH@ polyaniline core-shell nanocomposite array materials are widely used in supercapacitor electrode materials, lithium-ion batteries, zinc-ion batteries, electrochromic and photoelectrocatalytic fields;
[0026] 6. Utilizing the ion doping method prepared by the present invention to control defective MoO 3 Supercapacitors and electrochromic devices assembled with @NiCo-LDH@ polyaniline core-shell nanocomposite array materials have excellent cycle stability, specific capacity, energy density and power density. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 To utilize the ion doping prepared in Example 1 to control the defective MoO 3 Cyclic voltammetry curves of batteries composed of @NiCo-LDH@ polyaniline core-shell nanocomposite array materials at different potential windows;
[0028] Figure 2 The ion doping control of defective MoO prepared in Example 1 3 @NiCo-LDH@ polyaniline core-shell nanocomposite array material specific surface area and pore size distribution;
[0029] Figure 3 To utilize the ion doping prepared in Example 1 to control the defective MoO 3 @NiCo-LDH@ polyaniline core-shell nanocomposite array material specific capacity diagram under different current density conditions;
[0030] Figure 4 To utilize the ion doping prepared in Example 1 to control the defective MoO 3 @NiCo-LDH@polyaniline core-shell nanocomposite array material 5000 cycles stability test at current density 1A / g;
[0031] Figure 5 To utilize the ion doping prepared in Example 1 to control the defective MoO 3 @NiCo-LDH@polyaniline core-shell nanocomposite array material in the first test at a current density of 1A / g and the impedance diagram of the material after 5000 cycles;
[0032] Figure 6 To utilize the ion doping prepared in Example 1 to control the defective MoO3 Comparison of the first and last cycle of charge and discharge of @NiCo-LDH@ polyaniline core-shell nanocomposite array material at a current density of 1A / g, (a) is the first cycle, (b) is the last cycle;
[0033] Figure 7 The ion doping control of defective MoO prepared in Example 1 3 @NiCo-LDH@ polyaniline core-shell nanocomposite array material bending at different angles cyclic voltammetry curve test diagram;
[0034] Figure 8 To utilize the ion doping prepared by the present invention to control the defective MoO 3 Comparison of scanning electron microscopy images of the first and last circles of @NiCo-LDH@ polyaniline core-shell nanocomposite array material at a current density of 1A / g;
[0035] Fig. 9 To use the ion doping prepared in Example 1 to control the defective MoO 3 @NiCo-LDH@ polyaniline core-shell nanocomposite array material photocatalytic UV-visible light spectra of rhodamine B and methylene blue, where (a) is rhodamine B and (b) is methylene blue. DETAILED DESCRIPTION
[0036] Specific embodiment 1: This embodiment is a doping control defect-rich MoO 3 The preparation method of @NiCo-LDH@ polyaniline core-shell nanocomposite array material is specifically completed in the following steps:
[0037] 1. Preparation of MoO by low temperature water bath thermal method 3 :
[0038] ①. Put Na 2 MoO 4 The powder was added to deionized water and stirred for a while to obtain Na 2 MoO 4 Aqueous solution;
[0039] ② Use concentrated sulfuric acid or concentrated hydrochloric acid and water to prepare an acidic solution with a pH value of 1 to 6.5;
[0040] ③. Add an acidic solution with a pH value of 1 to 6.5 dropwise into the Na 2 MoO 4 The aqueous solution is stirred for a period of time to obtain a mixed solution; the mixed solution is heated at 40°C to 85°C for a period of time, and then cooled to room temperature to obtain a reaction product; the reaction product is washed and then dried to obtain MoO 3 powder;
[0041] 2. Preparation of ion-doped defect-rich MoO by cryo-preparation 3 @NiCo-LDH core-shell structure material:
[0042] ①、MoO 3 The powder, nickel salt, cobalt salt, alkaline substance and metal salt are added into deionized water, and ultrasonically mixed to obtain a precursor mixed solution;
[0043] ② Place the precursor mixed solution in a freeze dryer and freeze dry for a period of time. After the temperature of the reaction product returns to room temperature, wash, dry and plasma treat the reaction product. Finally, calcine at 350℃~850℃ for 2h~30h to obtain ion-doped defect-rich MoO 3 @NiCo-LDH core-shell structure material;
[0044] The specific process parameters of the plasma treatment described in step 2② are: using plasma technology, introducing oxygen gas, the treatment power is 100W to 1000W, and the treatment time is 5min to 30min;
[0045] 3. Preparation of MoO by Electrodeposition 3 @NiCo-LDH@Polyaniline core-shell nanocomposite array materials:
[0046] ①, adding polyaniline and lithium perchlorate into deionized water to obtain a deposition solution;
[0047] ② Ion-doped defect-rich MoO 3 @NiCo-LDH core-shell structure material is used as working electrode, Ag / AgCl is used as reference electrode, and Pt sheet is used as counter electrode. The working electrode, reference electrode and counter electrode are immersed in the deposition solution, and the deposition treatment is carried out for a period of time by constant current method. Then the working electrode is taken out, cleaned, dried, and finally annealed at 350℃~850℃ to obtain MoO 3 @NiCo-LDH@polyaniline core-shell nanocomposite array material;
[0048] 4. MoO 3 The surface of @NiCo-LDH@ polyaniline core-shell nanocomposite array material was plasma treated to change the surface properties and obtain doped and regulated defect-rich MoO 3 @NiCo-LDH@polyaniline core-shell nanocomposite array material;
[0049] The specific process parameters of the plasma treatment described in step 4 are: using plasma technology, introducing oxygen gas, the treatment power is 10W to 1000W, and the treatment time is 5min to 30min.
[0050] Specific implementation method 2: This implementation method is different from the specific implementation method 1 in that: the Na 2 MoO 4 The volume ratio of the amount of powder to deionized water is (0.01 mol to 5 mol): (20 mL to 500 mL); the stirring time in step 1① is 0.5 h to 8 h. The other steps are the same as those in the first embodiment.
[0051] Specific implementation method three: This implementation method is different from the specific implementation method one or two in that: the acidic solution with a pH value of 1 to 6.5 described in step 1③ is mixed with Na 2 MoO 4 The molar ratio of the aqueous solution is (0.02 mol to 0.5 mol): (0.01 mol to 5 mol); the stirring time in step 1③ is 0.5 h to 6 h. The other steps are the same as those in the specific implementation mode 1 or 2.
[0052] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: in step 1 ③, the mixed solution is heated at 40°C to 85°C for 2h to 50h; in step 1 ③, the reaction product is washed 2 to 4 times with deionized water and anhydrous ethanol respectively; the drying temperature in step 1 ③ is 40 to 80°C, and the drying time is 3h to 48h. The other steps are the same as those of specific embodiments 1 to 3.
[0053] Specific implementation method 5: This implementation method is different from specific implementation methods 1 to 4 in that: the nickel salt described in step 2① is nickel chloride, nickel sulfate or nickel nitrate; the cobalt salt described in step 2① is a mixture of one or both of cobalt chloride and cobalt nitrate; the alkaline substance described in step 2① is ammonia water, sodium hydroxide, potassium hydroxide or lithium hydroxide with a mass fraction of 25%; the metal salt described in step 2① is lanthanum chloride. The other steps are the same as those of specific implementation methods 1 to 4.
[0054] Specific embodiment 6: The difference between this embodiment and specific embodiments 1 to 5 is that: the precursor mixed solution in step 2① contains MoO 3 The concentration of the powder is 1g / L to 100g / L; the concentration of the nickel salt in the precursor mixed solution described in step 2① is 5g / L to 100g / L; the concentration of the cobalt salt in the precursor mixed solution described in step 2① is 0.1mol / L to 20mol / L; the concentration of the alkaline substance in the precursor mixed solution described in step 2① is 1g / L to 100g / L; the concentration of lanthanum chloride in the precursor mixed solution described in step 2① is 3g / L to 100g / L. The other steps are the same as those in specific embodiments 1 to 5.
[0055] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: the freeze-drying temperature in step 2 ② is -100℃~-180℃, the pressure is 25±1Pa, and the freeze-drying time is 3h~30h; the washing in step 2 ② is 3 to 7 times of deionized water; the drying temperature is 30℃~70℃, and the drying time is 5h~42h. The other steps are the same as those in specific embodiments 1 to 6.
[0056] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: the mass ratio of the polyaniline described in step three ① to the volume ratio of deionized water is (5g-40g): (20mL-1000mL); the mass ratio of the lithium perchlorate described in step three ① to the volume ratio of deionized water is (3g-35g): (20mL-1000mL); the constant current used for the deposition treatment in step three ② is 1mA-1000mA, and the deposition treatment time is 5min-30min; in step three ②, the working electrode is cleaned 3-4 times with water or anhydrous ethanol; the drying temperature is 30℃-70℃, and the drying time is 5h-40h; the annealing time at 350℃-850℃ in step three ② is 1h-12h. The other steps are the same as specific embodiments one to seven.
[0057] Specific embodiment 9: This embodiment is a doping control of defective MoO 3 @NiCo-LDH@polyaniline core-shell nanocomposite array materials are used as electrochromic materials or photoelectrocatalytic materials.
[0058] Specific embodiment 10: This embodiment is a doping control of defective MoO 3 @NiCo-LDH@polyaniline core-shell nanocomposite array materials are used as electrode materials in supercapacitors, lithium-ion batteries or zinc-ion batteries.
[0059] The following examples are used to verify the beneficial effects of the present invention:
[0060] Example 1: Ion doping to control defective MoO 3 The preparation method of @NiCo-LDH@ polyaniline core-shell nanocomposite array material is specifically completed in the following steps:
[0061] 1. Preparation of MoO by low temperature water bath thermal method 3 :
[0062] ①. Put Na 2 MoO 4 The powder was added to deionized water and stirred for 5 h to obtain Na 2 MoO 4 Aqueous solution;
[0063] Na described in step 1① 2 MoO 4 The volume ratio of the powder substance to deionized water is 0.03 mol:50 mL;
[0064] ② Use 36% concentrated hydrochloric acid and water to prepare an acidic solution with a pH value of 5;
[0065] ③. Add the acidic solution with pH value of 5 to the Na 2 MoO 4 The reaction product was washed with deionized water and anhydrous ethanol for 3 times, and then dried at 60°C for 22 hours to obtain MoO 3 powder;
[0066] The acidic solution with a pH value of 5 described in step 1③ and Na 2 MoO 4 The molar ratio of the aqueous solution is 0.05 mol:0.4 mol;
[0067] 2. Preparation of ion-doped defect-rich MoO by cryo-preparation 3 @NiCo-LDH core-shell structure material:
[0068] ①、MoO 3 The powder, nickel salt, cobalt salt, alkaline substance and metal salt are added into deionized water, and ultrasonically mixed to obtain a precursor mixed solution;
[0069] The nickel salt described in step 2① is nickel nitrate;
[0070] The cobalt salt described in step 2① is cobalt chloride;
[0071] The alkaline substance described in step 2① is sodium hydroxide;
[0072] The metal salt described in step 2① is lanthanum chloride;
[0073] MoO in the precursor mixed solution described in step 2① 3 The concentration of the powder is 72g / L;
[0074] The concentration of nickel salt in the precursor mixed solution described in step 2① is 34 g / L;
[0075] The concentration of cobalt salt in the precursor mixed solution described in step 2① is 0.5 mol / L;
[0076] The concentration of the alkaline substance in the precursor mixed solution described in step 2① is 25g / L;
[0077] The concentration of the metal salt in the precursor mixed solution described in step 2① is 30g / L;
[0078] ② Place the precursor mixed solution in a freeze dryer for freeze drying for a period of time, and then after the temperature of the reaction product returns to room temperature, wash, dry and plasma treat the reaction product, and finally calcine at 550 ° C for 25 h to obtain ion-doped defect-rich MoO 3 @NiCo-LDH core-shell structure material;
[0079] The freeze drying temperature in step 2② is -120°C, the pressure is 25±1Pa, and the freeze drying time is 12h;
[0080] The washing in step 2② is washing with deionized water for 5 times; the drying temperature is 55° C. and the drying time is 15 h;
[0081] The specific process parameters of the plasma treatment described in step 2② are: using microwave plasma, introducing oxygen gas, the treatment power is 600W, and the treatment time is 15min;
[0082] 3. Preparation of MoO by Electrodeposition 3 @NiCo-LDH@Polyaniline core-shell nanocomposite array materials:
[0083] ①, adding polyaniline and lithium perchlorate into deionized water to obtain a deposition solution;
[0084] The mass ratio of the polyaniline described in step 3① to the volume ratio of deionized water is 11 g:50 mL;
[0085] The mass ratio of lithium perchlorate described in step 3① to deionized water is 18g:60mL;
[0086] ② Ion-doped defect-rich MoO 3 @NiCo-LDH core-shell structure material is used as working electrode, Ag / AgCl is used as reference electrode, and Pt sheet is used as counter electrode. The working electrode, reference electrode and counter electrode are immersed in the deposition solution, and the deposition treatment is carried out for a period of time by constant current method. Then the working electrode is taken out, cleaned, dried, and finally annealed at 550℃ for 5h to obtain MoO 3 @NiCo-LDH@polyaniline core-shell nanocomposite array material;
[0087] In step 3②, the constant current used for the deposition process is 380 mA, and the deposition process time is 6 minutes;
[0088] In step 3②, the working electrode is cleaned 3 times with water or anhydrous ethanol; the drying temperature is 45°C and the drying time is 15h;
[0089] 4. MoO 3 @NiCo-LDH@polyaniline core-shell nanocomposite array material was plasma treated to obtain ion doping-controlled defective MoO 3 @NiCo-LDH@polyaniline core-shell nanocomposite array material;
[0090] The specific process parameters of the plasma treatment described in step 4 are: using plasma technology, introducing oxygen gas, the processing power is 600W, and the processing time is 25min.
[0091] Application Example 1: Using the ion doping prepared in Example 1 to control defective MoO 3 The battery assembled with @NiCo-LDH@ polyaniline core-shell nanocomposite array material is completed according to the following supplements:
[0092] Asymmetric supercapacitor assembly: ion doping and regulation of defective MoO prepared in Example 1 3 @NiCo-LDH@ polyaniline core-shell nanocomposite array material was used as the positive electrode, carbon nanotubes (CNTS) as the negative electrode, KOH solution as the electrolyte, and a separator was added between the positive and negative electrodes to prepare MoO 3 @NiCo-LDH@polyaniline / / CNTs asymmetric device. The geometric surface area of each electrode is 1cm 2 , using KOH solution as the electrolyte, the preparation of the electrolyte is to add 11.2g KOH into 150mL deionized water, and then stir continuously for 2h with a magnetic stirrer until the solution becomes transparent; soak the positive electrode, negative electrode material and separator in the electrolyte for 10min, then take them out from the electrolyte and assemble them together.
[0093] Figure 1 To utilize the ion doping prepared in Example 1 to control the defective MoO 3 Cyclic voltammetry curves of batteries composed of @NiCo-LDH@ polyaniline core-shell nanocomposite array materials at different potential windows;
[0094] Figure 1 MoO is shown 3 @NiCo-LDH@Polyaniline / / CNTs asymmetric device cyclic voltammetry curves of different voltage windows at a scan rate of 10mV / s. It can be clearly seen from the figure that the working voltage window can reach up to 1.6V, which indicates that the device can store and release more energy in a larger voltage range, thereby improving energy storage capacity and efficiency.
[0095] Figure 2 The ion doping control of defective MoO prepared in Example 1 3 @NiCo-LDH@ polyaniline core-shell nanocomposite array material specific surface area and pore size distribution;
[0096] from Figure 2 It can be seen that: the MoO 3 @NiCo-LDH@ polyaniline core-shell nanocomposite array material has a specific surface area of up to 156.7 m 2 / g. This large specific surface area provides a large contact area for the electrolyte, allowing sufficient contact between the electrolyte and the electrode material during the electrochemical reaction. Figure 2 In (b), we can observe the pore size distribution of the material, and it is obvious that the pore size is mainly concentrated around 15nm. This interwoven pore structure not only provides a channel for the rapid diffusion of electrolytes, but also increases the specific surface area of the material, further promoting the contact between electrolyte ions and electrode materials, thereby effectively improving the electrochemical activity and performance of the material.
[0097] Figure 3 To utilize the ion doping prepared in Example 1 to control the defective MoO 3 @NiCo-LDH@ polyaniline core-shell nanocomposite array material specific capacity diagram under different current density conditions;
[0098] from Figure 3 It can be seen that when the current density is 1, 2, 3, 5, and 8 A / g, MoO 3 @NiCo-LDH@Specific capacitance corresponding to polyaniline material. The discharge time and specific capacity of the material decrease with the increase of current density. This is because a small part of the material cannot fully participate in the reaction at high current density. However, the degree of reduction is still within a reasonable range, indicating that the material maintains good electrochemical properties at higher current density, showing excellent conductivity and structural stability.
[0099] Figure 4 To utilize the ion doping prepared in Example 1 to control the defective MoO 3 @NiCo-LDH@polyaniline core-shell nanocomposite array material 5000 cycles stability test at current density 1A / g;
[0100] from Figure 4 It can be seen that after 5000 cycles, the specific capacitance decreased from 1210F / g to 1142F / g, and the specific capacity retention rate was 94.3%, which indicates that MoO 3 @NiCo-LDH@polyaniline material has excellent cycling stability.
[0101] Figure 5 To utilize the ion doping prepared in Example 1 to control the defective MoO 3 @NiCo-LDH@polyaniline core-shell nanocomposite array material in the first test at a current density of 1A / g and the impedance diagram of the material after 5000 cycles;
[0102] from Figure 5 It can be seen that after 5000 cycles, only the slope of the curve changes slightly, which indicates that the diffusion capacity of the electrode becomes weaker but the change is not significant, indicating that MoO 3 @NiCo-LDH@polyaniline core-shell nanocomposite array material has long-term electrochemical stability.
[0103] Figure 6 To utilize the ion doping prepared in Example 1 to control the defective MoO 3 Comparison of the first and last cycle of charge and discharge of @NiCo-LDH@ polyaniline core-shell nanocomposite array material at a current density of 1A / g, (a) is the first cycle, (b) is the last cycle;
[0104] from Figure 6 It can be seen that there is no obvious change in the charge-discharge comparison diagram between the first cycle and the last cycle, indicating that the composite array material can still maintain good electrochemical properties after multiple charge-discharge cycles without obvious capacity decay or performance degradation.
[0105] Figure 7 The ion doping control of defective MoO prepared in Example 1 3 @NiCo-LDH@ polyaniline core-shell nanocomposite array material bending at different angles cyclic voltammetry curve test diagram;
[0106] from Figure 7 It can be seen that: MoO 3 After @NiCo-LDH@polyaniline was bent at different angles, the shape and characteristic peak position of the CV curve remained unchanged after bending, indicating that the electrochemical active sites of the material were not significantly reduced or inactivated due to bending. This shows that the material has excellent mechanical stability and structural toughness, and can maintain the stability of its electrochemical properties under different deformation states.
[0107] Figure 8 To utilize the ion doping prepared by the present invention to control the defective MoO 3 Comparison of scanning electron microscopy images of the first and last circles of @NiCo-LDH@ polyaniline core-shell nanocomposite array material at a current density of 1A / g;
[0108] from Figure 8It can be seen that the surface morphology of the material has not changed significantly, indicating that the material has good electrochemical stability under a current density of 1 A / g.
[0109] Application Example 2: Using the ion doping prepared in Example 1 to regulate defective MoO 3 @NiCo-LDH@ polyaniline core-shell nanocomposite array material degrades rhodamine B and methylene blue, specifically by the following steps:
[0110] Under the condition of simulated sunlight irradiation, 0.2 g of ion doping control defective MoO prepared in Example 1 was used in the experiment. 3 @NiCo-LDH@ polyaniline core-shell nanocomposite array material was added as a catalyst to 100 mL of 50 mg / L rhodamine B solution, and stirred thoroughly in the dark to achieve adsorption-desorption equilibrium. Under simulated daylight conditions, 5 mL of solution was taken from the solution every 5 minutes, and the catalyst was separated and removed from the suspension using a centrifuge, and then the absorbance value was tested using a UV-visible spectrophotometer;
[0111] Under the condition of simulated sunlight irradiation, 0.2 g of ion doping control defective MoO prepared in Example 1 was used in the experiment. 3 @NiCo-LDH@polyaniline core-shell nanocomposite array material was added as a catalyst to 100mL of 50mg / L methylene blue solution, and stirred thoroughly in the dark to allow complete mixing and achieve adsorption-desorption equilibrium. Under simulated daylight conditions, 5mL of solution was taken from the solution every 5min, and the catalyst was separated and removed from the suspension using a centrifuge, and then the absorbance value was tested using a UV-visible spectrophotometer.
[0112] Fig. 9 To use the ion doping prepared in Example 1 to control the defective MoO 3 The photocatalytic UV-visible spectra of @NiCo-LDH@ polyaniline core-shell nanocomposite array material on rhodamine B and methylene blue, (a) is rhodamine B, (b) is methylene blue;
[0113] from Fig. 9 It can be seen that the wavelengths with the strongest absorbance of rhodamine B and methylene blue are at 543nm and 672nm respectively. It can be seen that the nanomaterial MoO 3 The photocatalytic effect of @NiCo-LDH@ polyaniline is still very significant and fast. As can be seen from the figure, with the increase of degradation time, the absorbance values of rhodamine B and methylene blue gradually decrease, indicating that the dye is also gradually degrading. After a certain degradation time, MoO 3 The degradation rates of @NiCo-LDH@polyaniline were 93.2% and 96.8%, respectively.
Claims
1. A method for preparing a doping-controlled defective MoO3@NiCo-LDH@polyaniline core-shell nanocomposite array material, characterized in that The preparation method is specifically completed according to the following steps:
1. Preparation of MoO3 by low temperature water bath thermal method: ①. Add Na2MoO4 powder into deionized water and stir for a period of time to obtain Na2MoO4 aqueous solution; ② Use concentrated sulfuric acid or concentrated hydrochloric acid and water to prepare an acidic solution with a pH value of 1 to 6.5; ③. Drop an acidic solution with a pH value of 1 to 6.5 into a Na2MoO4 aqueous solution and stir for a period of time to obtain a mixed solution; heat the mixed solution at 40°C to 85°C for a period of time, and then cool it to room temperature to obtain a reaction product; wash the reaction product and then dry it to obtain MoO3 powder; 2. Preparation of ion-doped defect-rich MoO3@NiCo-LDH core-shell structure materials by freezing method: ①, add MoO3 powder, nickel salt, cobalt salt, alkaline substance and metal salt into deionized water, mix them evenly by ultrasonication, and obtain a precursor mixed solution; ②, the precursor mixed solution is placed in a freeze dryer for freeze drying for a period of time, and after the temperature of the reaction product returns to room temperature, the reaction product is washed, dried and plasma treated, and finally calcined at 350°C to 850°C for 2h to 30h to obtain an ion-doped defect-rich MoO3@NiCo-LDH core-shell structure material; The specific process parameters of the plasma treatment described in step 2② are: using plasma technology, introducing oxygen gas, the treatment power is 100W to 1000W, and the treatment time is 5min to 30min; 3. Preparation of MoO3@NiCo-LDH@polyaniline core-shell nanocomposite array materials by electrodeposition: ①, adding polyaniline and lithium perchlorate into deionized water to obtain a deposition solution; ②, using ion-doped defect-rich MoO3@NiCo-LDH core-shell structure material as working electrode, Ag / AgCl as reference electrode, and Pt sheet as counter electrode, immersing the working electrode, reference electrode and counter electrode into the deposition solution, and using constant current method for deposition for a period of time, then taking out the working electrode, cleaning the working electrode, drying it, and finally annealing it at 350℃~850℃ to obtain MoO3@NiCo-LDH@polyaniline core-shell nanocomposite array material; Fourth, the surface of the MoO3@NiCo-LDH@polyaniline core-shell nanocomposite array material is treated with plasma to change the surface properties, thereby obtaining a doped and regulated defect-rich MoO3@NiCo-LDH@polyaniline core-shell nanocomposite array material; The specific process parameters of the plasma treatment described in step 4 are: using plasma technology, introducing oxygen gas, the treatment power is 10W to 1000W, and the treatment time is 5min to 30min.
2. The method for preparing a doping-controlled defective MoO3@NiCo-LDH@polyaniline core-shell nanocomposite array material according to claim 1, characterized in that The volume ratio of the amount of Na2MoO4 powder described in step 1① to deionized water is (0.01mol~5mol):(20mL~500mL); the stirring time described in step 1① is 0.5h~8h.
3. The method for preparing a doping-controlled defective MoO3@NiCo-LDH@polyaniline core-shell nanocomposite array material according to claim 1, characterized in that The molar ratio of the acidic solution with a pH value of 1 to 6.5 and the Na2MoO4 aqueous solution described in step 1③ is (0.02mol to 0.5mol):(0.01mol to 5mol); the stirring time described in step 1③ is 0.5h to 6h.
4. The method for preparing a doping-controlled defective MoO3@NiCo-LDH@polyaniline core-shell nanocomposite array material according to claim 1, characterized in that In step 1③, the mixed solution is heated at 40℃~85℃ for 2h~50h; in step 1③, the reaction product is washed 2 to 4 times with deionized water and anhydrous ethanol respectively; the drying temperature in step 1③ is 40~80℃, and the drying time is 3h~48h.
5. The method for preparing a doping-controlled defective MoO3@NiCo-LDH@polyaniline core-shell nanocomposite array material according to claim 1, characterized in that The nickel salt described in step 2① is nickel chloride, nickel sulfate or nickel nitrate; the cobalt salt described in step 2① is a mixture of one or both of cobalt chloride and cobalt nitrate; the alkaline substance described in step 2① is ammonia water, sodium hydroxide, potassium hydroxide or lithium hydroxide with a mass fraction of 25%; the metal salt described in step 2① is lanthanum chloride.
6. The method for preparing a doping-controlled defective MoO3@NiCo-LDH@polyaniline core-shell nanocomposite array material according to claim 1, characterized in that The concentration of MoO3 powder in the precursor mixed solution described in step 2① is 1g / L~100g / L; the concentration of nickel salt in the precursor mixed solution described in step 2① is 5g / L~100g / L; the concentration of cobalt salt in the precursor mixed solution described in step 2① is 0.1mol / L~20mol / L; the concentration of alkaline substance in the precursor mixed solution described in step 2① is 1g / L~100g / L; the concentration of lanthanum chloride in the precursor mixed solution described in step 2① is 3g / L~100g / L.
7. The method for preparing a doping-controlled defective MoO3@NiCo-LDH@polyaniline core-shell nanocomposite array material according to claim 1, characterized in that The freeze-drying temperature described in step 2② is -100℃~-180℃, the pressure is 25±1Pa, and the freeze-drying time is 3h~30h; the washing described in step 2② is washing 3 times to 7 times with deionized water; the drying temperature is 30℃~70℃, and the drying time is 5h~42h.
8. The method for preparing a doping-controlled defective MoO3@NiCo-LDH@polyaniline core-shell nanocomposite array material according to claim 1, characterized in that The mass ratio of the polyaniline described in step 3① to the volume ratio of deionized water is (5g~40g):(20mL~1000mL); the mass ratio of the lithium perchlorate described in step 3① to the volume ratio of deionized water is (3g~35g):(20mL~1000mL); the constant current used for the deposition treatment in step 3② is 1mA~1000mA, and the deposition treatment time is 5min~30min; in step 3②, the working electrode is cleaned 3~4 times with water or anhydrous ethanol; the drying temperature is 30℃~70℃, and the drying time is 5h~40h; the annealing time at 350℃~850℃ in step 3② is 1h~12h.
9. Application of a method for preparing a doping-controlled defective MoO3@NiCo-LDH@polyaniline core-shell nanocomposite array material prepared by the preparation method according to claim 1, characterized in that A doped and regulated defective MoO3@NiCo-LDH@polyaniline core-shell nanocomposite array material is used as an electrochromic material or a photoelectrocatalytic material.
10. Application of a method for preparing a doped and regulated defective MoO3@NiCo-LDH@polyaniline core-shell nanocomposite array material prepared by the preparation method according to claim 1, characterized in that A doped and regulated defective MoO3@NiCo-LDH@polyaniline core-shell nanocomposite array material is used as an electrode material in supercapacitors, lithium-ion batteries or zinc-ion batteries.
Citation Information
Patent Citations
Ternary layered metal hydroxide@polyaniline composite electrode material and preparation method and application thereof
CN112542328A
NF@molybdenum oxide@nickel cobalt-LDH composite material, and preparation method and application thereof
CN113130214A
Preparation and application of PANI / MoO3-x shell-core composite electrode material with electrochromic function
CN113314354A
Preparation method of nickel-cobalt oxide@nickel-cobalt hydroxide core-shell structure electrode material
CN113421781A
Sodium borohydride reduced molybdenum-doped R-Mo-NiCo2O4 constructed by double-defect process and preparation method and application of sodium borohydride reduced molybdenum-doped R-Mo-NiCo2O4
CN114604906A
